2020
DOI: 10.4149/neo_2020_190321n255
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor is differentially expressed in normal and choriocarcinoma trophoblast cells

Abstract: Trophoblast cells are specific for placenta, the organ necessary for development of the fetus. Trophoblast derived choriocarcinoma is a rare cancer, with high metastatic potential, invading surrounding tissues and distant organs. Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine involved in a wide range of biological processes, which is increased in almost all human cancers. Expression of MIF in normal and choriocarcinoma trophoblast cells is investigated here, using normal extravillous tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The same research group also studied the potential contribution of trophoblast MIF on the spiral artery remodeling process. They demonstrated that attenuation of endogenous MIF by specific siRNA had a negative effect on the ability of HTR-8/SVneo to differentiate into endothelial-like phenotype [ 111 ]. HTR-8/SVneo cells also produce MIF in response to LPS, a cell wall constituent of most Gram-negative bacteria recognized by TLR4 [ 121 ].…”
Section: Mif In Normal and Pre-eclamptic Pregnancymentioning
confidence: 99%
“…The same research group also studied the potential contribution of trophoblast MIF on the spiral artery remodeling process. They demonstrated that attenuation of endogenous MIF by specific siRNA had a negative effect on the ability of HTR-8/SVneo to differentiate into endothelial-like phenotype [ 111 ]. HTR-8/SVneo cells also produce MIF in response to LPS, a cell wall constituent of most Gram-negative bacteria recognized by TLR4 [ 121 ].…”
Section: Mif In Normal and Pre-eclamptic Pregnancymentioning
confidence: 99%
“…The overexpression of MIF present in tumors not only confers an advantage in tumor growth but also confers a particular aggressiveness to tumor cells, allowing them to migrate and metastasize. The relationship between the MIF factor and tumorigenesis has been confirmed in various malignancies [ 6 , 8 ]. The level of MIF expression in most cancers correlates with tumor progression and the ability of cancer cells to spread [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human placenta choriocarcinoma is a highly malignant trophoblastic tumor characterized by abnormal trophoblastic hyperplasia, the absence of chorionic villi, hemorrhage, necrosis, and high metastatic potential [1,2]. Choriocarcinoma is a very rare neoplasm.…”
Section: Introductionmentioning
confidence: 99%